Collagen or Collagen-related Peptide Cause [Ca2+]i Elevation and Increased Tyrosine Phosphorylation in Human Megakaryocytes - Mountford, J. C.; Melford, S. K.; Bunce, C. M.; Gibbins, J.; Watson, S. P. (Thrombosis and Haemostasis, 1999)
Since megakaryocytes are the cellular precursors of platelets we have investigated whether they share responses to platelet agonists, in particular collagen. Although previous studies have reported responses to thrombin in non-human megakaryocytes, through studies of single cell calcium responses and protein tyrosine-phosphorylation we demonstrate for the first time that both isolated human megakaryocytes and CD41/61-positive megakaryocytes derived in culture from CD34+ cells share responses to the platelet agonists collagen, collagen-related peptide and thrombin. The responses to either collagen or CRP were seen only in the most mature megakaryocytes and not in mega-karyocyte-like cell lines, suggesting that the response to collagen is a characteristic developed late during megakaryocyte differentiation. These primary cells offer the opportunity to use many molecular and cellular techniques to study and manipulate signalling events in response to platelet receptor agonists, which cannot be performed in the small, anucleate platelet itself.